A Wireless Drive and Control Method for Robots: Multifrequency Microwaves - Yongze Li; Jianyu Wu; Lijun Zhao; Zhiguang Xing; Jianwen Zhao (Advanced Intelligent Systems, 2024)
Microwave (MW)‐driven strategies could potentially offer transmissivity through obstacles, selective energization, wave‐focusing, and nonmechanical steering via phased‐array technologies, which have unique application prospects in confined environments. Implementing multidegree of freedom (MDOF) control is the key to developing motion strategies for advanced MW‐driven robots. However, the use of MWs for MDOF control of robots has so far remained a challenge. This article first presents examples of wireless driving and controlling millimeter‐scale peristaltic pipeline robots (diameter, 4 mm; length, 30 mm; weight, 0.39 g) utilizing multifrequency MWs in complex nonmetal channel environments. Herein, shape memory alloy springs combined with passive wires, whose length depends on the frequencies of MWs, are adopted to form selectively controlled robot components, and silicon rubber replica technology is utilized to achieve miniaturization of the robot. The monopole antenna model is developed for the actuator, and its structure is refined using antenna theory. This allows the successfully achievement of MDOF control of the robot at several MW frequencies (2.4, 4, and 5.9 GHz). Powered by MWs from outside the pipe, the pipeline robot achieves horizontal, vertical, and curved motions in a pipe with a diameter of 5 mm.